Higher amyloid is associated with greater loneliness among cognitively normal older adults during the COVID-19 pandemic [version 2; peer review: 2 approved] - Susan Stark; Abigail Kehrer-Dunlap; Anne Fagan; Beau Ances; Audrey Keleman; Regina Thompson; Rebecca Bollinger; Szu-Wei Chen (F1000Research, 2024)
Background Loneliness has been associated with several consequences, including increased risk of developing Alzheimer disease (AD). Loneliness may arise during the preclinical phase of AD, but little is known about the relationship between loneliness and amyloid accumulation consistent with preclinical AD. Therefore, the purpose of this study was to examine the relationship between amyloid accumulation and subjective experiences of loneliness among cognitively normal older adults during the COVID-19 pandemic. Methods A global Clinical Dementia Rating ® Scale score of 0 was required for enrollment. Cortical amyloid burden was measured using [11C] Pittsburgh compound B or [18F]-Florbetapir PET tracers. Centiloids were used to synchronize measures. Demographic characteristics and measures of loneliness, anxiety, and depression were collected via self-report. Multiple linear regression was used to examine the relationship between loneliness and amyloid accumulation. Results The 108 participants had a mean age of 75.0 and an average amyloid accumulation of 22.2 ± 31.9. Mean UCLA Loneliness Scale scores were 31.6 ± 10.8. A significant positive association was detected between loneliness and amyloid accumulation (β = 0.064, SE = 0.027, 95% CI = [0.011, 0.118], p = 0.018). Conclusions These findings highlight the relationship between higher amyloid accumulation and greater loneliness during the COVID-19 pandemic. Healthcare professionals should include routine assessments for characteristics of loneliness in routine clinical evaluations and integrate loneliness reduction and prevention treatments among older adults experiencing loneliness. Additional research is needed with a larger, more diverse sample to examine the relationship between loneliness and amyloid accumulation.